Tree of life 2, trade mola - Unidentified artist (Colorado State University. Libraries, 1999)
The colors in this mola were chosen to appeal to tourist buyers.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Cotton; 2 layers (black, green); reverse and direct appliqué, embroidery.
Keywords: Molas -- Panama; Appliqué -- Panama; Embroidery -- Panama